Renewable Distributed Generation Models in Three-Phase Load Flow Analysis for Smart Grid - Syafii Syafii; K. M. Nor K. M. Nor (Universitas Ahmad Dahlan, 2013)
The paper presents renewable distributed generation (RDG) models as three-phase resource in load flow computation and analyzes their effect when they are connected in composite networks. The RDG models that have been considered comprise of photovoltaic (PV) and wind turbine generation (WTG). The voltage-controlled node and complex power injection node are used in the models. These improvement models are suitable for smart grid power system analysis. The combination of IEEE transmission and distribution data used to test and analyze the algorithm in solving balanced/unbalanced active systems. The combination of IEEE transmission data and IEEE test feeder are used to test the the algorithm for balanced and unbalanced multi-phase distribution system problem. The simulation results show that by increased number and size of RDG units have improved voltage profile and reduced system losses.